2011
DOI: 10.1093/her/cyq087
|View full text |Cite
|
Sign up to set email alerts
|

'Who is Helsinki?' Sex workers advise improving communication for good participatory practice in clinical trials

Abstract: After premature closures in 2004 of biomedical human immunodeficiency virus (HIV) prevention trials involving sex workers in Africa and Asia, the Joint United Nations Programme on HIV/AIDS (UNAIDS) and Global Advocacy for HIV Prevention (AVAC) undertook consultations to establish better participatory guidelines for such trials in order to address ethical concerns. This study investigated sex workers’ knowledge and beliefs about research ethics and good participatory practices (GPP) and the perspectives of sex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…In contrast, fewer studies conducted stakeholder engagement in middle‐ (30 studies; 27.8%) 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, 100 and low‐income (nine studies; 8.3%) 101, 102, 103, 104, 105, 106, 107, 108, 109 countries. The location of stakeholder engagement could not be discerned in six studies (5.6%) 110, 111, 112, 113, 114, 115, and fifteen studies (13.9%) 16, 24, 116, 117, 118, 119, 120, 121, 122, 123, 124, 125, 126, 127, 128 conducted stakeholder engagement in multiple countries at different income levels.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, fewer studies conducted stakeholder engagement in middle‐ (30 studies; 27.8%) 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, 100 and low‐income (nine studies; 8.3%) 101, 102, 103, 104, 105, 106, 107, 108, 109 countries. The location of stakeholder engagement could not be discerned in six studies (5.6%) 110, 111, 112, 113, 114, 115, and fifteen studies (13.9%) 16, 24, 116, 117, 118, 119, 120, 121, 122, 123, 124, 125, 126, 127, 128 conducted stakeholder engagement in multiple countries at different income levels.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to this work among drug using populations, to date, there has been less empirical attention to research ethics relevant experiences among FSW. The existing, but limited, work on the topic of research ethics among FSW has identified the issues of confidentiality, privacy, and respect as pertinent to this population; findings have indicated high levels of stigma and victimization as security challenges when conducting research among FSW (Shaver, 2005; Ditmore & Allman, 2011). However, the majority of these studies have not been specific to research ethics pertaining to HIV research among FSW.…”
mentioning
confidence: 99%
“…Furthermore, very few studies have occurred within high HIV prevalence Indian states, where a multitude of FSW directed HIV social and behavioral research studies have been conducted. Additionally, the existing work among FSW within this context, and elsewhere, has often been limited to studies focused on research ethics issues within vaccine or other HIV prevention trials (Suhadev et al, 2006; Ditmore & Allman, 2011; Berkley, 2008; Jayaraman, 2008; NIMH Collaborative HIV/STD Prevention Trial Group, 2007; Sahay & Mehendale, 2004; Thomas, 2004). In conclusion, less investigation on HIV research ethics issues (in India and elsewhere) has focused on the conduct of social and behavioral epidemiological studies, and this is particularly limited among FSW.…”
mentioning
confidence: 99%
“…Female sex workers are often subject to police raids, rape, violence, emotional abuse and marginalization (Platt et al, 2013; Shannon & Csete, 2010; Silverman, et al, 2011). As a result, recruitment, disclosure and participation of female sex workers in research are often compromised (Uusküla et al, 2010; Ditmore & Allman, 2011). Respect and relationality, the reciprocal ‘give and take’ relationship in which the researcher maintains the participant's trust (Fisher, 2011), are especially critical when conducting research with female sex workers.…”
mentioning
confidence: 99%
“…Care also needs to be taken to avoid “therapeutic misconception,” – the expectation from participants to personally gain over and above what they normally would receive from participating in the research (Fisher et al, 2008). To address these concerns, investigators have cited the need to be transparent about research aims and to provide participants with education, training, and familiarity with ethical research standards (Jeffreys, 2010; Ditmore & Allman, 2011). …”
mentioning
confidence: 99%